Overview of Passive Light Emitting Diode Driver Circuits for Street Lighting - R. Gunabalan (Institute of Advanced Engineering and Science, 2016)
This paper describes the overview and comparison of various passive Light Emitting Diode (LED) driver circuits employed for street lighting applications. Passive LED driver circuits are constructed with diodes and capacitors without using any power electronic semiconductor switches which in turn eliminates the secondary supply unit for control circuits and controllers. Passive LED driver circuits are simple in construction, low cost, less maintenance and control free. 50 W LED driver circuit is identified for performance comparison and simulations are performed in matlab- simulink to get an overview of different passive LED driver circuits. The most predominant parameters such as efficiency and total harmonic distortion are compared to identify the suitiblity of the driver circuits for various applications.